The extended Exton’s quadruple hypergeometric function K^(α,β)_15,p and its properties - Atash, Ahmed; Bellehaj, Hussein (Journal of Innovative Applied Mathematics and Computational Sciences, 2025)
In this paper, we introduce the extended Exton's hypergeometric function K^(α,β)_15,p using the extended beta function given by "Ozergin et al. For this extended function, we derive various properties, including integral representations, recurrence relations, generating functions, transformation formulas, and summation formulas. Some special cases of the main results are also considered.